Implementasi konsep kepemimpinan dalam manajemen pembelajaran praktik - Daniel Grace Christian (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe: 1) the concept of leadership implementation in learning management practices at LKP Solafide Semarang, 2) Supporting and inhibiting factors for the implementation of leadership concepts in practical learning at LKP Solafide Semarang, 3) the effectiveness of Semarang. This type of research is descriptive qualitative. Location at LKP Solafide Semarang. The data source was obtained at the location. The research subject is an instructor. The technique of interviewing data, observation and, documentation. Data analysis was carried out by using qualitative descriptive analysis, and data validity was performed by triangulation. The results show: 1) The teachers of LKP Solafide Semarang in learning management practices have implemented the concept of leadership in learning management practices at LKP Solafide Semarang, 2) Supporting factors for sinvolved human resources; Facilities and infrastructure in LKP, the inhibiting factor is incompetent teachers, and diverse students in various departments, 3) Effective implementation of leadership concepts in learning practices at LKP Solafide Semarang.